On the value of environmental pragmatism in economic decision-making : with special reference to the work of Bryan Norton - Seeliger, Leanne (Stellenbosch : University of Stellenbosch, 2009)
Thesis (DPhil (Philosophy))--University of Stellenbosch, 2009.